Hubungan antara Jarak Tanam dari Kawah Sikidang Dieng dengan Ukuran Sel Penutup dan Jumlah Stomata Daun Tanaman Kentang (Solanum tuberosum L) - Fitriani, Vicka; Haryanti, Sri; Darmanti, Sri (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2006)
The aims of this experiment was to know corelation of distance from Sikidang Dieng with the size cover cell of stomata and distribution of leaf stomata potato. Randimized Complete Design with 9 replicates were used to experiment. The treatment was distance 100 m from cauldron, 300 m, 500 m and 700 m. Parameter was size of cover cell and sum of stomata. The result of this experiment indicated that the more far from cauldron that size of cover cell the more long, while sum of stomata the more little.